Effects of duloxetine on pain and walking distance in neuropathic pain models via modulation of the spinal monoamine system. (26th September 2017) - Minami, K.; Tamano, R.; Kasai, E.; Oyama, H.; Hasegawa, M.; Shinohara, S.; Asaki, T.
Abstract: Background: Approximately 40% of patients with chronic low back pain have a neuropathic component. In this study, we assessed the effects of analgesics on tactile hypersensitivity and walking distance in the rat cauda equina compression (CEC) model of neuropathic low back pain. Methods: The effects of analgesics on tactile hypersensitivity were examined using the von Frey test in CEC and partial sciatic nerve ligation (pSNL) models. Effects on walking distance were assessed using a treadmill test. Levels of α2δ1 subunit and ATF‐3 mRNA in dorsal‐root ganglion (DRG) neurons and those of α2δ1 subunit protein in the spinal cord were determined using quantitative RT‐PCR and western blotting, respectively. Histological features were assessed using immunohistological methods. Results: Histological changes indicating nerve damage (increase in ATF‐3 mRNA, decrease in NF‐200 and an increase in CD68 immunoreactivity) were observed in the CEC model. Duloxetine had analgesic effects in both models and improved walking distance in the CEC model. Pregabalin had analgesic effects in both models; however, the effect was weaker in the CEC model than in the pSNL model. α2δ1 subunit expression in DRG neurons and in the spinal cord was unchanged in the CEC model, but significantly increased in the pSNL model. Indomethacin had no analgesic effect in either model. Intrathecal yohimbine inhibited the effects of duloxetine with significant effects on depression. Conclusions: These findings suggest that the analgesic effects of duloxetine are mainly mediated by the spinal monoamine system, independent of the antidepressant effects of this agent. Significance: The findings of this study suggest that duloxetine may be an effective treatment of broad neuropathic pain states, including neuropathic low back pain. The analgesic effects of duloxetine might be mediated by alterations of the descending pain modulatory pathways in the spinal cord, independent of the antidepressant effects.